Edukasi Plang Sampah sebagai Upaya Meningkatkan Kesadaran Lingkungan Masyarakat - Samsul Muarif; Alvonsus Rumampuk; Novi Rizky Ramadhani; Eben Ezer Sihombing; Indrawati Indrawati (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Waste management has become an increasingly complex environmental issue, particularly in urban areas and densely populated settlements. The lack of public awareness in disposing of waste properly has caused numerous negative impacts, including soil and water pollution, flooding due to clogged drainage systems, reduced environmental aesthetics, and the spread of infectious diseases. These conditions indicate that the waste problem is not merely a technical issue of collection and disposal, but also strongly related to people’s behavior and environmental awareness. Therefore, a simple, practical, and effective approach is required to encourage behavioral change in daily life. One alternative solution is through visual education by using waste signboards that display educational and persuasive messages. These signboards are installed in strategic locations to serve as direct reminders for residents to care more about environmental cleanliness. This study aims to analyze the effectiveness of waste education signboards in improving community understanding and discipline in waste disposal practices. The methods applied included counseling sessions, participatory discussions with residents, designing communicative and attractive signboards, and installing them in high-traffic areas such as main roads, schools, worship places, and public spaces. The results of the activity indicated an increase in public knowledge regarding the impacts of waste, active participation in maintaining cleanliness, and a significant reduction in littering behavior around the areas where the signboards were installed. Furthermore, residents gave positive feedback and expressed their willingness to expand the initiative by adding more signboards in other locations as part of sustainable action. In conclusion, educational signboards proved to be an effective, low-cost, and practical medium to raise community awareness. Beyond delivering environmental messages, the signboards also helped strengthen collective commitment among residents to create a clean, healthy, and sustainable living environment.